2010
DOI: 10.1128/jcm.01188-10
|View full text |Cite
|
Sign up to set email alerts
|

Rhino-Orbitocerebral Zygomycosis Caused by Conidiobolus incongruus in an Immunocompromised Patient in Germany

Abstract: Mucorales (subphylum Mucoromycotina) are well-known agents of invasive mucormycosis, whereas Entomophthorales (subphylum Entomophthoromycotina) are rarely encountered in human diseases in temperate zones. Here we report a fatal case of invasive rhino-orbitocerebral entomophthoramycosis caused by Conidiobolus incongruus in a 78-year-old woman with myelodysplastic syndrome. CASE REPORTA 78-year-old woman with known hypoplastic myelodysplastic syndrome (MDS) with trilinear pancytopenia was admitted to our hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…C. incongruus infection has been also diagnosed in sheep, causing rhinofacial infection (Ketterer et al 1992), and in a deer, causing systemic dissemination (Madson et al 2009). Thus, C. incongruus more commonly causes disseminated infections and seldom causes localized infection, a clinical feature in contrast to that of C. coronatus (Walker et al 1992;Walsh et al 1994;Wuppenhorst et al 2010).…”
Section: Lampraguesmentioning
confidence: 97%
See 2 more Smart Citations
“…C. incongruus infection has been also diagnosed in sheep, causing rhinofacial infection (Ketterer et al 1992), and in a deer, causing systemic dissemination (Madson et al 2009). Thus, C. incongruus more commonly causes disseminated infections and seldom causes localized infection, a clinical feature in contrast to that of C. coronatus (Walker et al 1992;Walsh et al 1994;Wuppenhorst et al 2010).…”
Section: Lampraguesmentioning
confidence: 97%
“…The first recorded case of C. incongruus infection in humans was diagnosed by Gilbert et al in 1970, but the recovered organism was properly identified 6 yr later by King and Jong (1976). C. incongruus infections have been diagnosed in both apparently normal and immunocompromised hosts (Walsh et al 1994;Wuppenhorst et al 2010). An important difference between C. incongruus and the other pathogenic Conidiobolus species is the clinical presentation of the infection.…”
Section: Lampraguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the rarity of those infections may have encouraged reports being made. [85][86][87][128][129][130][131][132][133][134][135][136][137][138] A relationship with the iron overload often seen in MDS cannot be ruled out, as iron overload is a known risk factor for zygomycosis infection (see above). In some cases, zygomycosis was observed at diagnosis of MDS.…”
Section: Invasive Fungal Infectionsmentioning
confidence: 99%
“…In some cases, zygomycosis was observed at diagnosis of MDS. 137,138 A significant number of patients had additional co-factors for zygomycosis, including diabetes, 137,138 obstructive bronchial pneumonia, 137 and treatment with deferoxamine. 85,87 In some cases, the clinical presentation was atypical, 139 with unusual features like spinal cord 131,135,140 or coronary artery obstruction.…”
Section: Invasive Fungal Infectionsmentioning
confidence: 99%